Severe Cushing’s syndrome due to small cell prostate carcinoma: a case and review of literature - M S Elston; V B Crawford; M Swarbrick; M S Dray; M Head; J V Conaglen (Endocrine Connections, 2017)
Cushing’s syndrome (CS) due to ectopic adrenocorticotrophic hormone (ACTH) is associated with a variety of tumours most of which arise in the thorax or abdomen. Prostate carcinoma is a rare but important cause of rapidly progressive CS. To report a case of severe CS due to ACTH production from prostate neuroendocrine carcinoma and summarise previous published cases. A 71-year-old male presented with profound hypokalaemia, oedema and new onset hypertension. The patient reported two weeks of weight gain, muscle weakness, labile mood and insomnia. CS due to ectopic ACTH production was confirmed with failure to suppress cortisol levels following low- and high-dose dexamethasone suppression tests in the presence of a markedly elevated ACTH and a normal pituitary MRI. Computed tomography demonstrated an enlarged prostate with features of malignancy, confirmed by MRI. Subsequent prostatic biopsy confirmed neuroendocrine carcinoma of small cell type and conventional adenocarcinoma of the prostate. Adrenal steroidogenesis blockade was commenced using ketoconazole and metyrapone. Complete biochemical control of CS and evidence of disease regression on imaging occurred after four cycles of chemotherapy with carboplatin and etoposide. By the sixth cycle, the patient demonstrated radiological progression followed by recurrence of CS and died nine months after initial presentation. Prostate neuroendocrine carcinoma is a rare cause of CS that can be rapidly fatal, and early aggressive treatment of the CS is important. In CS where the cause of EAS is unable to be identified, a pelvic source should be considered and imaging of the pelvis carefully reviewed.